2004
DOI: 10.5551/jat.11.341
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin and Pravastatin Elevated Pre-heparin Lipoprotein Lipase Mass of Type 2 Diabetes with Hypercholesterolemia

Abstract: To clarify whether 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitors (statin) increases lipoprotein lipase mass in preheparin plasma (preheparin LPL mass), we observed the change in preheparin LPL mass during administration of atorvastatin and pravastatin to type 2 diabetes mellitus patients with hypercholesterolemia. The subjects were randomly divided into two groups. One group was 24 patients given atorvastatin (10 mg/day), and the other was 23 patients given pravastatin (20 mg/day) for 4 months. Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 22 publications
(14 reference statements)
4
23
1
Order By: Relevance
“…This observation has been in line with the previous reports on the effects of this compound on LPL activity in PHP [45,46]. Recently, it has been reported that series of statins, such as pravastatins, atorvastatins and pitavastatins may produce a significant increase in serum LPL mass after the treatment [47,48]. An in vitro study has shown that that pitavastatins increase the expression of LPL mRNA from cultured 3T3 L1 cells [47].…”
Section: Effects Of Several Lipid-lowering Agents On Serum Lpl Masssupporting
confidence: 88%
“…This observation has been in line with the previous reports on the effects of this compound on LPL activity in PHP [45,46]. Recently, it has been reported that series of statins, such as pravastatins, atorvastatins and pitavastatins may produce a significant increase in serum LPL mass after the treatment [47,48]. An in vitro study has shown that that pitavastatins increase the expression of LPL mRNA from cultured 3T3 L1 cells [47].…”
Section: Effects Of Several Lipid-lowering Agents On Serum Lpl Masssupporting
confidence: 88%
“…Notably, statins increase LPL serum mass and activity in T2D (Endo et al. 2004). Perhaps these findings offer some explanation as to why some statins increase, albeit modestly, the risk of T2D(Thakker et al.…”
Section: Discussionmentioning
confidence: 99%
“…21 Administration of the potent statins simvastatin or atorvastatin to humans with hyperlipidemia and/or diabetes led to increases in preheparin LPL mass or post-heparin LPL activity in three out of four studies. [22][23][24][25] The weaker statin fluvastatin did not alter LPL activity in dyslipidemic subjects. 26 Given this evidence of statin modulation of LPL activity, the LPL haplotypes we analyzed may affect lipid response to statin by altering the responsiveness of LPL expression or activity to statins.…”
Section: Discussionmentioning
confidence: 99%